2016
DOI: 10.1002/acp.3222
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal Believers' Susceptibility to Confirmatory Versus Disconfirmatory Conjunctions

Abstract: SummaryThis study examines paranormal believers' susceptibility to the conjunction fallacy for confirmatory versus non‐confirmatory conjunctive events. Members of the UK public (N = 207) read 16 hypothetical vignettes before judging the likelihood that each constituent and their conjunction would (co) occur. Event type (paranormal versus non‐paranormal), outcome type (confirming versus disconfirming) and level of paranormal belief (in either extrasensory perception, psychokinesis or life after death)—plus rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 18 publications
4
26
1
Order By: Relevance
“…TPB includes concepts such as the devil, witchcraft, heaven and hell, and serves to regulate social/cultural factors (Goode, 2000). Similarly, Rogers et al (2016) noted that extrasensory perception and psychokinesis were associated with heightened susceptibility to generic conjunction fallacy. In this context, the nature of superstitious beliefs may predispose an association with conjunction error.…”
Section: Statistical Bias and Endorsement Of Conspiracy Theories 26mentioning
confidence: 96%
See 3 more Smart Citations
“…TPB includes concepts such as the devil, witchcraft, heaven and hell, and serves to regulate social/cultural factors (Goode, 2000). Similarly, Rogers et al (2016) noted that extrasensory perception and psychokinesis were associated with heightened susceptibility to generic conjunction fallacy. In this context, the nature of superstitious beliefs may predispose an association with conjunction error.…”
Section: Statistical Bias and Endorsement Of Conspiracy Theories 26mentioning
confidence: 96%
“…For instance, Dagnall et al (2014Dagnall et al ( , 2016 reported that conjunction error correlated only with TPB; the relationship with new age philosophy was not significant. Additionally, Rogers et al (2016) examined paranormal believers' susceptibility to conjunction fallacy for confirming versus disconfirming conjunctive events. Using ASGS factors, Rogers et al (2016) reported that belief in extrasensory perception & psychokinesis were associated with heightened susceptibility to generic conjunction fallacy, whilst life after death approached significance.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Tversky & Kahneman, 1974). Indeed, building on the biased probability judgment hypothesis, studies have shown that one specific probabilistic reasoning biasconjunction fallacyis prevalent among people with more paranormal (Prike, Arnold, & Williamson, 2017;Rogers, Davis, & Fisk, 2009;Rogers, Fisk, & Lowrie, 2016) and conspiracy beliefs (Brotherton & French, 2014). The relationship between probabilistic judgment and epistemically suspect beliefs, however, does not seem to be specific to the tendency to commit conjunction fallacy, as other probabilistic reasoning biases have also been shown to be associated with unwarranted beliefs (Dagnall, Drinkwater, Denovan, Parker, & Rowley, 2016;Dagnall, Drinkwater, Parker, & Rowley, 2014;Dagnall et al, 2007).…”
Section: Introductionmentioning
confidence: 99%